Technical Papers and Discussions - Aluminum and Aluminum Alloys - Low Cycle Fatigue of the Aluminum Alloy 24ST in Direct Stress (Metals Tech., Feb. 1948, TP 2338) With discussion - S. I. Liu; J. J. Lynch; E. J. Ripling; G. Sachs (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1949)
It is a generally recognized fact that by repeated straining the fracture stress of any metal is reduced to a fraction of its value for static loading. The value of this fatigue strength depends upon numerous factors, such as the states of strain and stress, the limits of straining, and the number of repeated loadings or cycles The large volume of previous investigations on fatigue is concerned entirely with large numbers of cycles, say exceeding 10,000 and up to 500,000,000. However, the changes in fracture stress and fracture strain occurring after a small number of repeated loadings have attracted little attention. Apparently the only investigations of this type are those byLudwik4.5 who subjected steel, copper, and aluminum wire to repeated torsion. In each test the torque was varied between identical values in the two directions of twisting. Depending upon the magnitude of the moment, fracturing occurred after a number of cycles, up to 10,000. The results of Ludwik's tests will be discussed later Such torsion does not readily yield actual stress and strain values. Therefore a pre- liminary study was made of the effects of repeated direct stresses, that is, tension and compression stresses. Because such tests are considerably more tedious than torsion tests, only high stresses were used in the preliminary work, yielding definite changes in metal properties after a few cycles. It was found in these tests that strains could be controlled more readily than stresses in the investigated range of high stresses. This paper, consequently, deals with the effects of strains of equal magnitude but different signs. The metal was first prestrained in static tension by a certain amount then subjected to compression to yield the same amount of strain after unloading. This loading cycle was repeated up to a maximum of seven times. After various cycles, the stress-strain curves in tension were determined, up to fracturing. As material for these tests, the aluniinum alloy 24ST was selected because it exhibits a comparatively small amount of necking in the tension rest This alloy permitted, therefore rather accurate cont.rol at the high strains necessary to produce fatigue failures at less than seven cycles. The results of this invest~gation appear sufliciently interesting to extend the method of attack in various directions It is intended to study (11 the effects of cycles up to a tew thousands and (2) the effects of strains of different magnitude in tension and compression respectively 'The latter variable also includes a. a special case the effects of compressive strains.